Gaining national belonging Argentinians and Ecuadorians in Spain and Italy - García, Paola; Garzón, Luis (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Taking as a starting point the fieldwork undertaken between 2002 and 2006 in three cities of southern Europe, the questions of identity and national belonging of Argentinians and Ecuadorians in Spain and Italy are addressed. The concept of national belonging is made up of three separate dimensions: access to citizenship, access to the labor market and feeling of belonging and identity. Our fieldwork shows that from the two groups, Argentinians do have access to national belonging of the host society with greater ease, something that entails further advantages in their process of integration. However, there are different shades according to the possibility of attaining citizenship and labor market integration, in addition to differences to the legal framework of foreign law and the perceived proximity or distance to the culture of the host country. National belonging, far from being a fixed data, is shown to be changing along the biographic trajectory
Keywords: Argentinean; Ecuadorian; National belonging